Inferior Vena Cava Filters: Guidelines, Best Practice, and Expanding Indications - DeYoung, Elliot; Minocha, Jeet (Seminars in Interventional Radiology, 2016)
Vena caval interruption, currently accomplished by percutaneous image-guided insertion of an inferior vena cava (IVC) filter, is an important therapeutic option in the management of selected patients with venous thromboembolism. The availability of optional (or retrievable) filters, in particular, has altered the practice patterns for IVC filters, with a shift to these devices and expansion of indications for filter placement. As new devices have become available and clinicians have become more familiar and comfortable with IVC filters, the indications for filter placement have continued to evolve and expand. This article reviews current guidelines and expanding indications for IVC filter placement.
Keywords: inferior vena cava filters; indications; guidelines; interventional radiology